Efficacy and safety of laser acupuncture on osteoarthritis: a systematic review and meta-analysis - Xiangdong Wen; Guojiang Zhang; Jinquan Cui; Yuzhe Tang; Qi Meng; Yang Su; Senbo An; Shui Sun; Shui Sun (Frontiers in Aging Neuroscience)
ObjectivesTo perform a meta-analysis of previous studies investigating the effects of laser acupuncture on osteoarthritis.Study designSystematic review and meta-analysis.MethodsRandomized controlled trials (RCTS) on laser acupuncture for osteoarthritis were searched in the databases of PubMed, Embase, Cochrane Library, and Web of Science with a search deadline of 24 December 2023. After identifying 11 studies, we used Stata 15.0 to analyze the data.ResultsIn the 11 studies identified, 931 patients were analyzed. Results showed that laser acupuncture significantly improved patients’ pain and function compared to the placebo laser group. There were significant differences in VAS pain scores[SMD = −0.924, 95% CI (−1.200, −0.649), p = 0.000], WOMAC pain scores[SMD = −0.425, 95% CI (−0.652, −0.199), p = 0.000], WOMAC function scores[SMD = −0.307, 95% CI (−0.548, −0.065), p = 0.013], WOMAC stiffness scores[SMD = −0.235, 95% CI (−0.388, −0.083), p = 0.002] between the laser acupuncture group and the placebo laser group. The therapeutic effect of laser acupuncture disappeared at 8 weeks. In subgroup analysis, patients who received laser acupuncture with specific parameters had better VAS scores and WOMAC scores than patients in other subgroups.ConclusionThe application of laser acupuncture can improve knee pain and function in patients with osteoarthritis in the short term. It is recommended to use a laser with a power greater than 100 mW and a wavelength greater than 1,000 nm. CO2 lasers and solid-state lasers were shown to be more effective in the results than other types of lasers.